APPLICATION OF BLOCKCHAIN TECHNOLOGIES IN ENTERPRISE FINANCIAL ACTIVITIES: PROSPECTS AND CHALLENGES (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The rapid development of technology is significantly transforming all spheres of human activity, and the financial industry is no exception. Recent decades have been marked by the emergence and rapid spread of blockchain technologies, which promise to revolutionize traditional approaches to doing business. From decentralized finance (DeFi) to smart contracts and asset tokenization, blockchain opens up unprecedented opportunities to increase transparency, security, efficiency, and reduce operational costs.Purpose: a comprehensive analysis of the prospects and challenges of applying blockchain technologies in the financial activities of enterprises, as well as substantiation of their role in increasing the efficiency, transparency, and security of corporate finances in the modern digital economy.Methods. To achieve the goal, our research will be based on the integrated application of a number of scientific methods. Analysis and synthesis will become the foundation for an in-depth study of existing scientific papers, reports and analytical materials related to the implementation of blockchain technologies in the financial sphere. Through analysis, we can break down complex concepts into components, and synthesis will help to combine the data into a single, holistic picture. A systems approach will allow us to consider the financial activities of enterprises integrating blockchain as a complex interconnected system, assessing the impact of the technology on various aspects of business operations and identifying potential synergies and risks.Results. In this scientific article, the conducted research deeply delves into the scope of application of blockchain technologies in the financial activities of enterprises, revealing both their significant transformational potential and significant challenges on the path to implementation.Conclusions: The application of blockchain technologies in the financial activities of enterprises has enormous potential for the transformation and optimization of many processes. From increased transparency and security to automation and access to new sources of funding, the benefits are clear. However, successful blockchain integration requires careful analysis, overcoming regulatory and technical challenges, and significant investment in skills development.
Keywords: blockchain, digital transformation, smart contracts, cybersecurity, efficiency.